Concordance between genetic relatedness and phenotypic similarities of Trichomonas vaginalis strains - Hampl, V; Vanácová, S; Kulda, J; Flegr, J (BMC evolutionary biology, 2001)
BACKGROUND: Despite the medical importance of trichomoniasis, little is known about the genetic relatedness of Trichomonas vaginalis strains with similar biological characteristics. Furthermore, the distribution of endobionts such as mycoplasmas or Trichomonas vaginalis virus (TVV) in the T. vaginalis metapopulation is poorly characterised. RESULTS: We assayed the relationship between 20 strains of T. vaginalis from 8 countries using the Random Amplified Polymorphic DNA (RAPD) analysis with 27 random primers. The genealogical tree was constructed and its bootstrap values were computed using the program FreeTree. Using the permutation tail probability tests we found that the topology of the tree reflected both the pattern of resistance to metronidazole (the major anti-trichomonal drug) (p < 0.01) and the pattern of infection of strains by mycoplasmas (p < 0.05). However, the tree did not reflect pattern of virulence, geographic origin or infection by TVV. Despite low bootstrap support for many branches, the significant clustering of strains with similar drug susceptibility suggests that the tree approaches the true genealogy of strains. The clustering of mycoplasma positive strains may be an experimental artifact, caused by shared RAPD characters which are dependent on the presence of mycoplasma DNA. CONCLUSIONS: Our results confirmed both the suitability of the RAPD technique for genealogical studies in T. vaginalis and previous conclusions on the relatedness of metronidazol resistant strains. However, our studies indicate that testing analysed strains for the presence of endobionts and assessment of the robustness of tree topologies by bootstrap analysis seem to be obligatory steps in such analyses.
Keywords: mykoplazmové infekce; Male; trichomonádová vaginitida; druhová specificita; protozoální DNA; Mice, Inbred C57BL; RNA-viry; Animals; Phenotype; Humans; DNA, Protozoan; Mice; myši inbrední C57BL; Species Specificity; mužské pohlaví; Female; Mycoplasma; Mycoplasma Infections; polymorfismus genetický; ženské pohlaví; Polymorphism, Genetic; zvířata; fylogeneze; Virulence; RNA Viruses; Random Amplified Polymorphic DNA Technique; virulence; lidé; Trichomonas vaginalis; technika náhodné amplifikace polymorfní DNA; Phylogeny; fenotyp; Trichomonas Vaginitis; myši